Perancangan Sistem Informasi Strategik Pada XYZ Untuk Memaksimalkan Pemasaran Dan Efisiensi Biaya - Elizabeth Elizabeth; Agus Zainul Arifin (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2017)
ThegoalofwritingthisresearchistoMaximize Marketing Through E-Commerce Small Mediun Enterprise (SME) XYZ.The structureofcomposingthisresearchisrefersofmethodologyITStrategicPlanning which created by John Ward andPeppard in the bookThe Strategic Management of Information Systems (2016).Theanalysis startwithcompany’scondition usinginternalanalysis tools such as SWOT andexternal analysis tools such as PEST and Porter Analysis, Internal Environment IS/IT,External Environment IS/IT. Theresultoftheanalysis arethenprocessedandlatergenerate initiatives in form of IS Business Strategies, IS/IT Management Strategies, andIT Strategies. From that analysis result can take a summary and recommendfor ISBusiness Strategy arecreateWebsite E-Commerce with Cloud Computing Cozy andintegrated with BI (Business Intelligence)Google Analytics, InstallSMSGatewayGammu, and optimalizeonlinemarketing with social media. ForIS/ITmanagementstrategy are analysis cost and benefit from this project. IT Strategy analysis arerecommend software and IT Roadmap.